#TITLE_ALTERNATIVE# - aini1 (NIM:01 03 031), Nur
Abstract: The modeling of gas flow through the transmission pipe is often done using an assumption that the flow is in a steady state, the condition for which the gas flows independent of time. However, there are some situations for which steady state assumption is not valid anymore. Then the transient non isothermal gas flow can adequately be applied to this condition. The transient flow model here govern the continuity, the momentum, and the energy equations, together with the real gas equation of state. Those equations, especially the continuity, the momentum, and the energy equations are nonlinear conservative hyperbolic partial differential equations, and if we combined them together with real gas equation of state, it will become a nonlinear hyperbolic partial differential system. Those equations are hard to solve analytically due to the properties of that system which are nonlinear and hyperbolic. As an alternative, a numerical method can be used to determine its solution. In this final project the Lax wendroff numerical scheme will be applied to compute the distributions of the gas pressure, gas flow rate, and gas temperature. The steady state condition is used as the initial condition and the observation field data as the boundary conditions. The main objective in this final project is to predict the distribution of the gas flow properties, such as the gas pressure, gas flow rate, and gas temperature via numerical simulations.